Pengaruh Terapi Spiritual Murottal Pada Klien Risiko Perilaku Kekerasan Di Rsj Prof. Dr. Hb Saanin Padang Tahun 2025 - Wahyuni Muna Aprilia; Edo Gusdiansyah; Amelia Susanti (CV. ITTC INDONESIA, 2026)
The risk of violent behavior is a common psychiatric nursing problem in schizophrenia patients. At Prof. Dr. HB Saanin Mental Hospital in Padang, this prevalence remains high despite patients receiving general therapy, including physical, pharmacological, verbal, and spiritual therapy. An initial survey of ten patients showed that most still experienced physical and emotional symptoms, such as flushing, tense expressions, and verbal outbursts of anger. This suggests the need for additional spiritual interventions, one of which is Quranic recitation therapy. This study aims to determine the effect of spiritual recitation therapy on reducing the risk of violent behavior. This study used a quantitative approach with a pre-experimental design of one group pretest-posttest. The study sample consisted of 30 patients diagnosed with a risk of violent behavior who were treated in the Merpati and Flamboyan Wards of Prof. Dr. HB Saanin Mental Hospital, Padang. The sampling technique used purposive sampling according to the inclusion and exclusion criteria. Data collection was carried out using the RUFA observation sheet and analyzed using the parametric paired t-test. The results of the study showed that the average score of signs and symptoms in patients at risk of violent behavior before being given murottal therapy was 11.83 where the average respondent was in the intensive II category (moderate) while after therapy it increased to 18.40 where the average respondent was in the intensive II category (moderate). The results of the paired t-test showed a p value = 0.000, which means there was a significant influence between before and after murottal spiritual therapy on reducing symptoms of violence in patients. The conclusion of this study is that murottal spiritual therapy is effective in reducing signs and symptoms in patients at risk of violent behavior. Therefore, it is recommended that psychiatric nurses integrate murottal spiritual therapy as an intervention modality in psychiatric nursing practice to accompany generalist therapy for optimal results.